2021
DOI: 10.3389/fgene.2021.627907
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Circular RNA Expression Deregulation at the Transition to Recurrent Spontaneous Seizures in Experimental Temporal Lobe Epilepsy

Abstract: Mesial temporal lobe epilepsy (mTLE) is a common form of epilepsy and is characterized by recurrent spontaneous seizures originating from the temporal lobe. The majority of mTLE patients develop pharmacoresistance to available anti-epileptic drugs (AEDs) while exhibiting severe pathological changes that can include hippocampal atrophy, neuronal death, gliosis and chronic seizures. The molecular mechanisms leading to mTLE remain incompletely understood, but are known to include defects in post-transcriptional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 114 publications
(151 reference statements)
3
16
0
Order By: Relevance
“…Unfortunately, their specific neuronal functions remain poorly understood. Our own work and that of others shows deregulated expression of circRNAs in mTLE patients and in experimental models of epilepsy (e.g., Gong et al, 2018 ; Lee et al, 2018 ; Li et al, 2018 ; Gray et al, 2020 ; Gomes-Duarte et al, 2021 ). For example, we have recently reported enrichment of circRNA deregulation at the transition to recurrent spontaneous seizures ( Gomes-Duarte et al, 2021 ).…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Unfortunately, their specific neuronal functions remain poorly understood. Our own work and that of others shows deregulated expression of circRNAs in mTLE patients and in experimental models of epilepsy (e.g., Gong et al, 2018 ; Lee et al, 2018 ; Li et al, 2018 ; Gray et al, 2020 ; Gomes-Duarte et al, 2021 ). For example, we have recently reported enrichment of circRNA deregulation at the transition to recurrent spontaneous seizures ( Gomes-Duarte et al, 2021 ).…”
Section: Introductionsupporting
confidence: 64%
“…Library preparation and circRNA analysis using RNA-seq were performed as described previously ( Gomes-Duarte et al, 2021 ), with minor modifications (human circRNA detection). Purified RNA (2 μg input) was depleted of ribosomal RNA (rRNA) using the Ribo-Zero Magnetic Kit (human/mouse/rat; Illumina).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another experiment interestingly demonstrated that overexpressed circ-DROSHA weakened the neural damage of the TLE cell model (71). A recent study also confirmed the altered circRNAs expression during epileptogenesis (61). If circRNAs could impair paradoxical discharge, TLE would be suppressed.…”
Section: Epilepsymentioning
confidence: 89%
“…The potential of RNA for the treatment of neurodegenerative diseases is under constant investigation, as demonstrated by very recent studies in this field. [ 303 ] Positive outcomes have motivated researchers to identify strategies for aiding the delivery of RNA, injected locally into the brain or at a systemic level, for the treatment of these diseases. [ 304 , 305 , 306 ] To be suitable for this specific application, a proper design of delivery systems is required to provide them in vivo stability and transcytotic potential.…”
Section: Rna Delivery Applicationsmentioning
confidence: 99%